The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/lubricants7060047
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Power Loss and Lubrication of Connecting Rod Big-End

Abstract: A hydrodynamic lubrication analysis for connecting rod big-end bearing is conducted. The effects of engine speed, operating condition, lubricant viscosity and oil temperature on tribological performance of big-end bearing have been examined. Force equilibrium is solved to define instantaneous eccentricity between journal and bearing to have accurate estimation of oil film thickness at interface of connecting rod big-end bearing and crankpin. Connecting rod big-end is treated as π film hydrodynamic journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(33 reference statements)
2
2
0
Order By: Relevance
“…The similar behaviour has also been reported by Razavykia et al. 48 that the power loss decreases with the reduction in viscosity and moreover, temperature rise is more for higher viscosity oils at higher eccentricity ratios. Further, it is evident that power loss is increased with increase in concentration of nanoparticles and this is attributed to the fact that on increasing the nanoparticle concentration, resistance offered by viscous force get increased which results increase in friction force and hence power loss as explained in Kalakada et al.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The similar behaviour has also been reported by Razavykia et al. 48 that the power loss decreases with the reduction in viscosity and moreover, temperature rise is more for higher viscosity oils at higher eccentricity ratios. Further, it is evident that power loss is increased with increase in concentration of nanoparticles and this is attributed to the fact that on increasing the nanoparticle concentration, resistance offered by viscous force get increased which results increase in friction force and hence power loss as explained in Kalakada et al.…”
Section: Resultssupporting
confidence: 89%
“…It has been found that power loss increases with increase in viscosity of lubricants but its value is slightly decreased with increase in eccentricity ratio for LO2 and LO3 based lubricants having higher viscosities. The similar behaviour has also been reported by Razavykia et al 48 that the power loss decreases with the reduction in viscosity and moreover, temperature rise is more for higher viscosity oils at higher eccentricity ratios. Further, it is evident that power loss is increased with increase in concentration of nanoparticles and this is attributed to the fact that on increasing the nanoparticle concentration, resistance offered by viscous force get increased which results increase in friction force and hence power loss as explained in Kalakada et al 21 Although direct comparison of static performance characteristics results obtained in this study cannot be substantially made due to the considerations of different journal bearing configurations and operating parameters in the literature, some researchers have studied the effect of nanolubricants on THD analysis of journal bearings.…”
Section: Power Loss Calculationssupporting
confidence: 89%
“…Razavykia et al used a hydrodynamic lubrication model to evaluate the tribological performance of connecting rod big-end bearings, and the instantaneous eccentricity between the journal and bearing was calculated using Newton-Raphson's scheme. The finite difference method was applied to calculate hydrodynamic pressure at connecting rod big-end and crankpin interface as well as frictional power loss [14].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the counterweights produces a change in the reaction forces and in the loading diagram of each journal bearing. Therefore, once the counterweight configuration has been defined, it is of paramount importance to evaluate how this change may influence the design of the journal bearings themselves [10][11][12][13], an aspect which is, however, beyond the scope of the present work.…”
Section: Introductionmentioning
confidence: 99%